Effect of mixed cropping of alfalfa and red clover on population density and infestation rate of alfalfa weevil Hypera postica (Col.: Curculionidae) - S. Roshandel; S. Noorbakhshian (نامه انجمن حشره‌شناسی ایران, 2016)
Population density and infestation rate of alfalfa weevil Hypera postica L. in mixed cropping of alfalfa (Medicago sativa L.) and red clover (Trifolium pretense L.)were evaluated. Different rates of alfalfa (Al) and red clover (RC) RC0AL100, RC20AL80, RC40AL60, RC50AL50, RC60AL40, RC80AL20 and RC0AL100 were studied as treatments.Using standard sweep nets, sampling was carried out weekly and data analyzed in Randomize Complete Block Design. Damage and infestation rates of alfalfa weevil were caculated by inspection of 20 stem tips of alfalfa in each plot. The results showed that forage yield was higher in mixed treatments comparing to pure alfalfa and red clover treatments (p = 0.01). Average number of alfalfa larvae, pest population and infestation percentage were significantly lower in mixed treatments in comparison with pure alfalfa (p = 0.01). Average dry weight was significant in pure alfalfa treatment (p = 0.01). Alfalfa weevil larvae and adults were not observed feeding at pure red clover treatments. Increase of red clover amount, led to higher average dry weight. In mixed treatments, the infestation and damage percentage decreased, but the yield increased. It is concluded that using 20-40% red clover (RC20AL80, RC40AL60) treatments efficiently increase the yield and reduce the damage of the pest.